The Maldives in transition : human rights and voices of dissent - Didi, Aminath (Curtin University, 2013)
This thesis explores the factors that have facilitated and inhibited the Maldives transition to a human rights respecting nation. The death of a young inmate in Maafushi Jail in September 2003 triggered events that led the Maldives to accept international human rights norms and to revise its Constitution. It also led the Maldives to embrace pluralistic democracy leading to the fall of a thirty-year dictatorial regime in 2008. Data gathered through interviews with activists and dissidents, as well as policy and law makers were analysed using grounded theory methodology.Increasing domestic opposition as well as international pressure from transnational advocacy networks and international aid donors steered the Maldives from a path of relative isolation in the 20th century, into the globalised world of the 21st century. Through the use of modern means of communication, the opposition took to direct action on the streets to bring about a regime change. The findings from the data highlight some of the challenges facing the Maldives in its transitioning from authoritarian to democratic rule. Voice has been given to dissent through this research. Key challenges still remain for the country to move forward in its path to democracy and human rights.